Gouvernance participative et agriculture biologique en Île-de-France - Nicolas Boivin; André Torre (Territoire en Mouvement)
The territorial environmental stakes believes in an exponential way for a decade. The political decision-makers seize this sphere of influence and facilitate actions which promote the sustainable project. The Paris Region chooses to base its territorial development partially on the "greening urban" ideology. This Region operates actions to become the first European Ecoregion by half-dozen years. It facilitates agro-environmental decisions. One of the pillars of this territorial development is organic farming. To create a dynamics of local democracy, the Paris Region establishes participative governance based on debates, on Round Tables and public reports. This paper suggests analyzing the means used to create participative dynamics in the town and country planning, in the territorial management. This "governmentality" of the organic farming strengthens the plan of suburban farming to interest the urban voters.